How many miles can Sarah travel in 6 hours
The equation relating distance, d, to time, t, is given by d = 55t, where 55 is the constant of variation. Sarah can travel 330 miles in 6 hours by substituting t = 6 into the equation d = 55t.
The equation that relates the distance, d, to the time, t, when they vary directly is:
d = k * t
where k represents the constant of variation.
To find the value of k, we can use the given information. Sarah travels 440 miles in 8 hours. Substituting these values into the equation:
440 = k * 8
Dividing both sides by 8:
k = 440 / 8
k = 55
Therefore, the equation that relates the distance, d, to the time, t, is:
d = 55t
To find how many miles Sarah can travel in 6 hours, we substitute t = 6 into the equation:
d = 55 * 6
d = 330
Therefore, Sarah can travel 330 miles in 6 hours.
To know more about equation:
#SPJ2
Answer:
d=55t Sara travels 330 miles
Step-by-step explanation:
We are given that distance, d, Sarah drives varies directly to the time, t. This means
d=k⋅t
for some constant, k. Since Sarah travels 440 miles in 8 hours, we substitute these values into the formula for direct variation to find
440=k⋅8
Dividing by 8 gives k=55, so an equation that relates d and t is
d=55t
Substituting t=6 yields
55(6)=330
So Sarah can travel 330 miles in 6 hours.
Answer:
25,095238095 = 25 2⁄21
Step-by-step explanation:
Just multiply each denominator and numerator straight across and convert to a mixed number, decimal, or whatever you want.
I am joyous to assist you anytime.
pls help me thanks
To see if the point is on the line, plug in one of the point values to see if it equals out.
y = 4x - 2 I will plug in 1 for x to see if y does = 3
y = 4(1) - 2
y = 4 - 2
y = 2 so (1, 2)
Dinesh is not correct because the point on the line when x = 1 is (1, 2) not (1, 3)
Answer: 7
Step-by-step explanation:
To find the distance between the two point, we simply use this formular:
D = √ (x₂ -x₁)² + (y₂ - y₁ )²
x₁ = -4 y₁ =3 x₂=-4 y₂ = -4
D = √(-4-[-4])² + (-4-3)²
(-4-[-4])²= (-4+4)²=(0)²=0
(-4-3)² = 49
D = √0+49
D= √49
The square root of 49 is 7
D=7
Therefore the distance between (-4 3) and (-4 -4) is 7